An overview of the role of MMP-8 and ADAM-33 in bronchial asthma - Kahan Celik; Tanya Tacheva; Dimo Dimov; Tatyana Vlaykova (Biotechnology & Biotechnological Equipment)
Matrix metalloproteinases (MMPs) and A disintegrin and metalloproteinases (ADAMs) are enzymes able to degrade a variety of protein components of the extracellular matrix. Due to the diverse role of MMPs and ADAMs, they are involved in the pathogenesis of many diseases, including chronic inflammatory lung diseases. In this review, the objective is to summarize the current knowledge about the role of the two enzymes from the respective families, namely MMP-8 and ADAM-33, in Bronchial asthma in order to explore the possibility for their expression, polymorphisms or serum/BAL (Bronchoalveolar Lavage) concentration to be used as biomarkers or targets for future target therapy. Considering the key functions of MMP-8 and ADAM-33 in many pathologic conditions, development of proper inhibitors of their action might be useful tools in the treatment approaches. However, a lot of knowledge has yet to be gained about these enzymes and their role in bronchial asthma, since some of the mechanisms are unknown or not discovered yet.